2021
DOI: 10.3233/jad-201176
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Low-Density Lipoprotein Cholesterol Levels, Statin Use, and Dementia in Patients followed in German General Practices

Abstract: Background: No studies have been conducted to date on the association between low-density lipoprotein cholesterol (LDL-C), statin use classified into low, medium, and high statin dosages, and dementia in German general practices. Objective: The goal of this retrospective case-control study was to investigate the relationship between elevated LDL-C, statins, and dementia in elderly persons followed in general practices in Germany. Methods: This study included patients aged 65 or older with an initial dementia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In Germany, the sampling methods used to select physicians’ practices are appropriate for obtaining a representative database of general and specialized practices. 13 Finally, this database has already been used in previous studies focusing on diabetes 14 as well as NAFLD. 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Germany, the sampling methods used to select physicians’ practices are appropriate for obtaining a representative database of general and specialized practices. 13 Finally, this database has already been used in previous studies focusing on diabetes 14 as well as NAFLD. 15 …”
Section: Methodsmentioning
confidence: 99%
“…In Germany, the sampling methods used to select physicians' practices are appropriate for obtaining a representative database of general and specialized practices. 13 Finally, this database has already been used in previous studies focusing on diabetes 14 as well as NAFLD. 15 Study population This retrospective cohort study included adult patients (≥18 years) with an initial diagnosis of T2D (index date) and at least one antihyperglycemic prescription between January 2012 and December 2018.…”
Section: Databasementioning
confidence: 99%
“…It has previously been shown that the panel of practices included in the Disease Analyzer database is representative of general and specialized practices in Germany [6]. Finally, this database has already been used in previous studies focusing on digestive system diseases [7][8][9][10].…”
Section: Databasementioning
confidence: 99%
“…Regarding lipid profile, there is no clear consensus, although statin treatment has been shown to reduce the risk of dementia in cohort studies [ 35 , 36 , 37 , 38 ]. Evidence suggests that high total cholesterol levels in mid-life increased the risk of AD in later life [ 6 ].…”
Section: Discussionmentioning
confidence: 99%